Allergen exposure modifies the relation of sensitization to FENO levels in children at risk for allergy and asthma - Sordillo, Joanne E (2011)
BACKGROUND: Studies on airway inflammation, measured as fraction exhaled nitric oxide (FENO), have focused on its relation to control of asthma, but the contribution of allergen exposure to elevation of FENO is unknown. OBJECTIVE: We evaluated (1) whether FENO was elevated in children with allergic sensitization or asthma; (2) whether specific allergen exposure increased FENO levels in sensitized, but not in unsensitized children; and (3) whether sedentary behavior increased FENO, independent of allergen exposures. METHODS: At age 12, in a birth cohort of children with parental history of allergy or asthma, we measured bed dust allergen (dust mite, cat, cockroach) by ELISA; specific allergic sensitization primarily by specific IgE ; and respiratory disease (current asthma, rhinitis, and wheeze) and hours of TV viewing/video game playing by questionnaire. Children performed spirometry maneuvers before and after bronchodilator responses, and had FENO measured using electrochemical detection methods (NIOX MINO). RESULTS: FENO was elevated in children with current asthma (32.2 ppb), wheeze (27.0 ppb), or rhinitis (23.2ppb) as compared to individuals without these respective symptoms/diagnoses (16.4 ppb to 16.6 ppb, p< 0.005 for all comparisons). Allergic sensitization to indoor allergens (cat, dog, dust mite) predicted higher levels of FENO, and explained one third of the variability of FENO. FENO levels were highest in children both sensitized and exposed to dust mite. Greater than 10 hours of weekday TV viewing was associated with a 0.64 log increase in FENO, after controlling indoor allergen exposure, BMI and allergic sensitization. CONCLUSION: Allergen exposures and sedentary behavior (TV viewing/ video game playing), may increase airway inflammation, measured as FENO.